2019
DOI: 10.1111/1751-7915.13421
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny‐guided characterization of glycosyltransferases for epothilone glycosylation

Abstract: Summary Glycosylation of natural products can influence their pharmacological properties, and efficient glycosyltransferases (GTs) are critical for this purpose. The polyketide epothilones are potent anti‐tumour compounds, and YjiC is the only reported GT for the glycosylation of epothilone. In this study, we phylogenetically analysed 8261 GTs deposited in CAZy database and revealed that YjiC locates in a subbranch of the Macrolide I group, forming the YjiC‐subbranch with 160 GT sequences. We demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…1 H and 13 C-NMR data assigned 1a as midecamycin 2′- O -glucopyranoside ( Table 1 , Figures S2–S6 ), suggesting OleD preferred to attack 2′-OH in mycaminosyl moiety of midecamycin. In addition, OleD was able to glucosylate 2′-OH of oleandomycin [ 25 , 26 , 27 , 28 , 38 , 39 , 40 ]. These facts collectively indicated that 2′-OH might be the preferred site of glycosylation for macrolides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H and 13 C-NMR data assigned 1a as midecamycin 2′- O -glucopyranoside ( Table 1 , Figures S2–S6 ), suggesting OleD preferred to attack 2′-OH in mycaminosyl moiety of midecamycin. In addition, OleD was able to glucosylate 2′-OH of oleandomycin [ 25 , 26 , 27 , 28 , 38 , 39 , 40 ]. These facts collectively indicated that 2′-OH might be the preferred site of glycosylation for macrolides.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse macrolide-inactivating GTs had been isolated and functionally identified. The exemplifying macrolide-inactivating GTs were OleI and OleD from S. antibioticus [ 31 ], MGT from S. lividans [ 25 ], BaGT from Bacillus atrophaeus , BamGT from B. amyloliquefaciens , BcGT-1 from B.cereus , BgGT from B. glycinifermentans , BpGT from B. paralicheniformis , as well as BsGT-1 and BssGT from B. subtilis [ 38 , 39 ]. These GTs have been demonstrated to be acceptor promiscuous, recognizing multiple macrolides.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis SCK6 was used as the heterologous expression host. 21 Bacillus sp. LCB12 was previously isolated from alkaline soil.…”
Section: Bacterial Strains Plasmids and Mediamentioning
confidence: 99%
“…[28] The recombination fragment was obtained by overlap-extension PCR and transformed into B. subtilis strains by a previously described method. [29] The following antibiotics were used for selection: kanamycin (30 μg mL −1 ) and zeocin (30 μg mL −1 ). The positive clones were identified by PCR amplification by primers AlsSDLF and AlsSDRR and further confirmed by sequence analysis.…”
Section: Gene Deletionmentioning
confidence: 99%